Isolation of Vaccine-Like Poliovirus Strains in Sewage Samples From the United Kingdom. (22nd December 2017) - Majumdar, Manasi; Klapsa, Dimitra; Wilton, Thomas; Akello, Joyce; Anscombe, Catherine; Allen, David; Mee, Edward T; Minor, Philip D; Martin, Javier
Abstract: Background: Environmental surveillance (ES) is a sensitive method for detecting human enterovirus (HEV) circulation, and it is used worldwide to support global polio eradication. We describe a novel ES approach using next-generation sequencing (NGS) to identify HEVs in sewage samples collected in London, United Kingdom, from June 2016 to May 2017. Methods: Two different methods were used to process raw sewage specimens: a 2-phase aqueous separation system and size exclusion by filtration and centrifugation. HEVs were isolated using cell cultures and analyzed using NGS. Results: Type 1 and 3 vaccine-like poliovirus (PV) strains were detected in samples collected from September 2016 through January 2017. NGS analysis allowed us to rapidly obtain whole-genome sequences of PV and non-PV HEV strains. As many as 6 virus strains from different HEV serotypes were identified in a single cell culture flask. PV isolates contained only a small number of mutations from vaccine strains commonly seen in early isolates from vaccinees. Conclusions: Our ES setup has high sensitivity for polio and non-PV HEV detection, generating nearly whole-genome sequence information. Such ES systems provide critical information to assist the polio eradication endgame and contribute to the improvement of our understanding of HEV circulation patterns in humans. Abstract : We describe the isolation of vaccine-like poliovirus in sewage samples using concentration methods followed by cell culture infection and next generation sequencing. Using this approach, we rapidly obtained whole-genome sequences of polio and nonpoliovirus enterovirus strains present in mixtures.